Preservice Science Teachers’ Perceptions of Learning Difficulties in Organic Chemistry at an Indonesian University - Fatma Wati; Ade Sazaliana (UNIVERSITAS NEGERI MEDAN, 2026)
This study examined preservice science teachers’ perceptions of learning difficulties in Organic Chemistry and their relationship with achievement in General Chemistry. A quantitative descriptive–correlational design was employed. The participants were 103 undergraduate students enrolled in the Science Education program who were taking an Organic Chemistry course, selected through total sampling. Data were collected using a four-point Likert-scale questionnaire measuring perceived learning difficulties and analyzed using SPSS 23. The results indicated that students’ perceptions of learning difficulties were distributed across high and low levels. Among the assessed indicators, problem-solving and analytical skills were perceived as the most challenging. No significant differences were found in perceptions based on gender. Meanwhile, a significant positive correlation was identified between General Chemistry achievement and perceived learning difficulties in Organic Chemistry (R² = 0.91), indicating a strong association within the study sample. However, this association should be interpreted cautiously due to the correlational design of the study. These findings suggest that students’ understanding of foundational chemistry concepts plays a crucial role in shaping their learning experiences in Organic Chemistry and should be strengthened to support more effective instruction.